Relationship Between Work Stress And Temporomandibular Disorders Risk In Productive Age (Study On Dental Clinical Students Of Sriwijaya University) - Rani Purba; Ashrinda Dita Mutiara; Pudji Handayani (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2020)
Introduction: It is known that stress is one of the risk factors for Temporomandibular Disorders (TMD) occurrence. Dental education programs are universally known to be demanding and can cause stress among dental students particularly dental clinical students. The study of the relationship between stress in dental clinical students and TMD risk has not been done yet. This study aimed to assess the relationship between work stress and TMD risk in productive age (study on dental clinical students of UNSRI Palembang). Materials and Methods: A cross-sectional study was performed towards 80 dental clinical students of Sriwijaya University (UNSRI) aged 21-28. The subjects were instructed to fill two kinds of questionnaire, the first one was Dental Environment Stress (DES) to examine the level of dental clinical student’ stress, the other was TMD Diagnostic Index (TMD-DI) to assess the TMD risk. Correlation hypothesis test analysis was carried out between the work stress level of dental clinic students and the risk of TMD. Results: Pearson's correlation test showed a significant correlation between stress in dental clinic students and the risk of TMD. The Pearson correlation coefficient (r) was 0,724. Conclusion:There was a significant relationship between stress in dental clinical students and the risk of TMD.